In Silico Molecular Docking Studies on Rhodanine Derivatives as a Potential Aldose Reductase Inhibitors - Neelam Khan; Javed Khan Pathan (Novel Aspects on Pharmaceutical Research Vol. 7, 2023)
An in silico study was performed on a set of rhodanine compounds (TA-01 to TA-11) as potential aldose reductase inhibitors (ARI) for the management of diabetes mellitus complications. Protein flexibility, multiple ligand binding modes and the free-energy landscape profile for binding affinity prediction are important and interconnected challenges to be overcome by further methodological developments in the docking field. In this investigation, molecular docking of rhodanine analogs against aldose reductases was performed using MVD software within the active site region of 4lua. The binding free energy (kcal/mol) was determined by the aforementioned compounds. The ligand-protein inverse docking simulation technique was performed with 11 synthetic ligands rhodanine derivatives with basic \(α\), \(β\)-unsaturated ketone and oxa thiazole moieties reported to be having aldose reductase inhibitory activity by using MVD program. The docking results of a set of rhodanine compounds showed that the most stable binding ligand TA-01 (TA01-TA-11) with a Moldock score of -147.01 kcal/mol involved with selected aldose reductase crystal structures shows that it forms hydrogen bonds with at least 3 hydrogen bonds with key active site residues Thr 113, Trp 111, Gln 49 within the binding site region of 4lua. The future discovery of powerful aldose reductase inhibitors for the treatment of diabetes may result from these molecular docking analyses. According to a docking investigation, the rhodanine analogue (TA-01) interacts with aldose reductase (ALR) through hydrogen bonds. The interaction causes the ALR-rhodanine complex to become stable.